Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have the following problem:

Let $f:\Bbb R^2\to \Bbb R$ be $C^1$ and $c>0$. Evaluate $\lim_{t\to 0} {{1}\over {t}}\int_{-ct}^{ct} f(t,u)du$, if this limit exists. If it does not, say why.

Well, the following was how I approached it:

First, let $F(t,u)$ be the function ${d\over du}F(t,u)=f(t,u)$. Then: $$\lim_{t\to 0} {{1}\over {t}}\int_{-ct}^{ct} f(t,u)du=\lim_{t\to 0} {{1}\over {t}} F(t,u)|_{-ct}^{ct}=\lim_{t\to 0} {{1}\over {t}}[F(t,ct)-F(t,-ct)]=2c\lim_{t\to 0} {{1}\over {2ct}}[F(t,ct)-F(t,-ct)]=2cf(0,0).$$

Thus, the conclusion I will get is the limit exists and is equal to $2cf(0,0)$. I wonder whether this approach is right or not. Thanks.

share|cite|improve this question
Each choice of $f$ and $c$ gives a different limit problem, so uniqueness of limit only applies when you compute different values for the limit with the same $f$ and same $c$. – Hurkyl Feb 24 '13 at 3:34
Ah, yes! You are definitely right. I will fix it and ask for suggestions. – Scorpio19891119 Feb 24 '13 at 3:40
@Hurkyl How it looks now? – Scorpio19891119 Feb 24 '13 at 3:51
It will be easier/cleaner to prove the limit exists by directly using the continuity of $f(x,y)$ at $(0,0)$. If $|f(x,y) - f(0,0)| < \epsilon$ over a neighborhood of $(0,0)$. If $t$ is small enough such the the line segment between $(t,-ct)$ to $(t,ct)$ falls inside this neighborhood, you can show $|\frac{1}{t}\int_{-ct}^{ct}f(t,u)du - 2cf(0,0)| \le 2c\epsilon$. – achille hui Feb 24 '13 at 5:13

You have the right answer, but I'm not sure I follow your reasoning.

If $\phi(x) = \int_0^{g(x)} f(x,u) du$, then (assuming $f,g$ are sufficiently smooth) we have $\phi'(x) = f(x,{g(x)})g'(x) + \int_0^{g(x)} \frac{\partial f(x, u)} {\partial x} du$.

Let $F(t) = \int_{-ct}^{ct} f(t,u) du = \int_{-ct}^{0} f(t,u) du + \int_{0}^{ct} f(t,u) du = - \int_0^{-ct} f(t,u) du + \int_{0}^{ct} f(t,u) du$. Then using the above we get $F'(t) = -f(t,-ct)(-c)+f(t,ct)(c)+ \int_{-ct}^{ct} \frac{\partial f(t, u)} {\partial x} du$.

The desired value is $F'(0)$ which is $F'(0) = 2 c f(0,0)$.

share|cite|improve this answer

I think you have the right idea.

When you define $F(t,u)$, you really mean

$$ \frac{\partial}{\partial u} F(t,u) = f(t,u) $$

I confess I prefer the notation $F_2(t,u)$, where "$F_2$" means "the derivative of $F$ with respect to its second argument" for reasons that will be made clear shortly.

So you computed the integral correctly and got that the limit is

$$ \lim_{t \to 0} \frac{F(t, ct) - F(t, -ct)}{t} $$

and it's the right idea that this looks very much like a limit for computing a derivative.

If we were asked to compute the limit

$$ \lim_{u \to 0} \frac{F(t, cu) - F(t, -cu)}{u} $$

then this is indeed equal to

$$ \lim_{u \to 0} \frac{F(t, cu) - F(t, -cu)}{u} = 2c F_2(t, 0) = 2c \frac{\partial}{\partial u} F(t,u) \mid_{u=0} $$

(Notice how awkward partial derivative notation is becoming!) But that's not actually what we're computing! Your idea of computation is effectively to compute

$$ \lim_{t \to 0} \lim_{u \to 0} \frac{F(t, cu) - F(t, -cu)}{u} $$

but the thing we actually want to compute can be written as

$$ \lim_{t \to 0} \lim_{u \to t} \frac{F(t, cu) - F(t, -cu)}{u} $$

Are we sure these are equal? The answer would be yes if the following limit exists:

$$ \lim_{(t,u) \to (0,0)} \frac{F(t, cu) - F(t, -cu)}{u} $$

Alas I'm rusty on my analysis. There's probably some theorem that says this should definitely be true because $F(t,u)$ is continuously differentiable in a neighborhood of $(0,0)$, but it doesn't spring to mind.

So I'll get my hands dirty and do a differential approximation. Rather than prove the full theorem, I'll do just the limit we're interested in

$$ \lim_{t \to 0} \frac{F(t, ct) - F(t, -ct)}{t} $$ $$ = \lim_{t \to 0} \frac{F(0,0) + t F_1(0,0) + ct F_2(0,0) - F(0,0) - t F_1(0,0) + ct F_2(0,0) + o(t) }{t} $$ $$ = \lim_{t \to 0} 2c F_2(0,0) + o(1) = 2c F_2(0,0) = 2c f(0,0)$$

where I've used little-oh notation to represent the error terms conveniently. It's clear from this calculation why we need $f$ to be differentiable! And you should check that $F(t,u)$ is also continuously differentiable.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.